THE DETERMINANT FACTOR OF CROWDFUNDERS' BEHAVIOUR IN USING CROWDFUNDING WAQF MODEL: CASE STUDY IN GENERATION Z MUHAMMADIYAH - Sayuti, Hendri; Syamsurizal; Zaimsyah, Annisa Masruri; Masrizal (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
Introduction: The potential of Waqf is vast in Indonesia but has yet to be optimized. This paper offers a model for waqf institutions to adopt financial technology to develop Waqf for Muhammadiyah organizations. Later, the Crowdfunding waqf model (CWM) was validated by adopting the technology acceptance model (TAM) theory. Methods: This research adopts a structural equation using the partial least square approach to test the hypothesis. Based on purposive sampling, 568 questionnaires were distributed through an online survey to Generation Z Muhammadiyah. Results: Based on the findings, the Crowdfunding waqf model's perceived benefits and ease of use positively impact waqf institution trust and crowdfunder or donor behavioral intention. Furthermore, the results also found that literacy and religiosity significantly positively affect crowdfunding behavioral intentions in Waqf. Conclusion and suggestion: The results of this study provide a comprehensive perspective for policymakers, especially Muhammadiyah organizations, to improve quality by adopting crowdfunding financial technology in raising waqf funds. Finally, this paper offers additional literature on Waqf and Crowdfunding, particularly in the context of religious organizations.